(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The prevalence of obesity in school-aged children and adolescents has risen to more than 10-fold over the past 40 years. (World Obesity Atlas 2022). Childhood obesity is one of the most serious public health challenges of the 21st century. The problem is global and is steadily affecting many low and middle income countries, particularly in urban and rural settings. The present study was undertaken to know Knowledge and Attitude related to overweight and obesity among rural school children. Self constructed questionnaire was administered to school children studying in 6th and 7th grade in rural area of Dharwad district, Karnataka. The results highlight various gaps in knowledge and attitudes regarding diet and health which was related to overweight and obesity. There is a need for comprehensive education and awareness initiatives to promote healthier dietary habits and combat misconceptions about food and nutrition. And there is also a need for increased education and awareness about the importance of physical activity in preventing and managing overweight and obesity, particularly among children.